PENEGAKAN HUKUM TERHADAP PENYELENGGARA JALAN YANG RUSAK YANG MENGAKIBATKAN KECELAKAAN LALU LINTAS DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA PEKANBARU - Tua, Paratama Mangihut; Yophie, Syaifullah; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Organizers Pekanbaru City Road as the authorities and must execute the order of Law Number 22 Year 2009 on Traffic and Transportation to refining the damaged roads. If the damaged roads has claimed the lives of physically and materially, the organizers may be liable and required role Pekanbaru City Police to conduct law enforcement. The purpose of this study namely; First, the rule of law against the organizers of the road traffic accident which resulted in the jurisdiction Pekanbaru City Police, Second, obstacles in the implementation of law enforcement against the organizers of damaged roads resulting in traffic accidents by the police in the jurisdiction in Pekanbaru City Police, Third , the efforts made to overcome the obstacles in the implementation of law enforcement against the organizers of the road that led to the accident by the police in the jurisdiction in Pekanbaru City Police.This research was conducted in Pekanbaru City Police and Department of Public Works City of Pekanbaru, while the population and the sample is a whole party relating to the issues examined in this study, which used data sources, primary data, secondary data, and the data tertiary, technical data collection in this study conducted by interviews, questionnaires, and literature study.From the research, there are three things that are inferred. First Law enforcement against the organizers of the road traffic accident which resulted in the jurisdiction in Pekanbaru City Police conducted through the efforts preentif, preventive and repressive. Secondly, bottlenecks in the implementation of such a lack of law enforcement personnel, lack of community participation, lack of traction on law enforcement, and the lack of public knowledge about the rules broken. Third, efforts were made to overcome such obstacles is an act providing guidance, supervision to members and coordinate with other authorities against bad roads in the city of Pekanbaru. Advice Author, First, Pekanbaru City Police should take a clear stance in enforcing the law to the organizers, the Second, the need for socialization and deepening understanding of related integrated legislation related to damaged roads laka unit members then, Thirdly, other law enforcement expected also plays an active role in protecting the rights of society as a road user.